Overexpression of POLQ confers a poor prognosis in early breast cancer patients - Higgins, Geoff S; Harris, Adrian L; Prevo, Remko; Helleday, Thomas; McKenna, W Gillies; Buffa, Francesca M (Oncotarget, 2010)
Depletion of POLQ (DNA polymerase theta) has recently been shown to render tumour cells more sensitive to radiotherapy whilst having little or no effect on normal tissues. This finding led us to investigate whether tumours that overexpress POLQ are associated with an adverse outcome. We therefore correlated the clinical outcomes of two retrospective series of patients with early breast cancer with the expression levels of POLQ, as determined by microarray gene expression analysis. We found that a significant number of tumours overexpressed POLQ and that overexpression was correlated with ER negative disease (p=0.047) and high tumour grade (p=0.004), both of which are associated with poor clinical outcomes. POLQ overexpression was associated with poor relapse free survival rates on both univariate (HR 5.80; 95% CI, 2.220 to 15.159; p<0.001) and multivariate analysis (HR 8.086; 95% CI 2.340 to 27.948 p=0.001). Analysis of other published clinical series confirmed that POLQ overexpression is associated with adverse clinical outcomes. The poor prognosis associated with POLQ is independent of other clinical or pathological features. The mechanism that causes this adverse outcome remains to be elucidated but may in part arise from resistance to adjuvant treatment. These findings, combined with the limited normal tissue expression of POLQ, make it a very appealing target for possible clinical exploitation.